Survival of patients with chronic ischemic heart disease depending оn the type of adaptational reaction - Radchenko, Elena; Filipyuk, Anzhelika; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Radchenko Elena, Filipyuk Anzhelika, Zukow Walery. Survival of patients with chronic ischemic heart disease depending оn the type of adaptational reaction. Journal of Education, Health and Sport. 2015;5(2):125-132. ISSN 2391-8306. DOI: 10.5281/zenodo.15687 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A125-132 https://pbn.nauka.gov.pl/works/541144 http://dx.doi.org/10.5281/zenodo.15687 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015. UDС: 616.12-005.4-037:616-003.96 SURVIVAL OF PATIENTS WITH CHRONIC ISCHEMIC HEART DISEASE DEPENDING ОN THE TYPE OF ADAPTATIONAL REACTION Elena Radchenko1, Anzhelika Filipyuk1, Walery Zukow2 1Danylo Halytsky Lviv National Medical University, Lviv, Ukraine 2Kazimierz Wielki University, Bydgoszcz, Poland Corresponding Authors: Elena Radchenko, Doctor of Medical Sciences, Professor, Head of Department of Internal Medicine №2, Danylo Halytsky Lviv National Medical University Anzhelika Filipyuk, Candidate of Medical Sciences, Danylo Halytsky Lviv National Medical University e-mail: Filipyuk_a@ukr.net Abstract The aim of investigations was to study survival of patients with chronic ischemic heart disease (IHD) depending of the type of adaptational reaction. It was studied correlations between the type of adaptational reactions and the clinical course of chronic IHD in 121 male patients in long-term prospective observation. The diagnosis of IHD was based on clinical examinations, laboratory investigations, electrocardiography, echocardiography, exercise testing, coronary angiography. It was revealed, that distress-reactions (stress, over-activation and defective adaptation) are significant predictors of an unfavorable chronic IHD prognosis. They were associated with acute cardiovascular events onset, functional class III of chronic heart failure, prothrombotic disorders of coagulation haemostasis (high levels of fibrinogen, fibrin-monomer and D-dimer), and dyslipidemia (lower HDL-cholesterol values). Decreasing оf lymphocyte/neutrophil ratio (index of adaptation) is аn informative parameter of distress-reactions and a significant predictor of an unfavorable chronic IHD course. Key words: adaptational reactions, stress, ischemic heart disease prognosis, fibrin-monomers, lymphocyte/neutrophil ratio.